Synthesis of a Nitrogenase P-N-Cluster Model with [Fe8S7(mu-S-thiolate)(2)] Core from the All-Ferric [Fe4S4(S-thiolate)(4)] Cubane Synthon - Moula, Golam; Nagasaki, Ayaka; Matsumoto, Tsuyoshi; Miehlich, Matthias; Meyer, Karsten; Cramer, Roger E.; Tatsumi, Kazuyuki (Angewandte Chemie International Edition, 2021)
Constructing synthetic models of the nitrogenase P-N-cluster has been a long-standing synthetic challenge. Here, we report an optimal nitrogenase P-N-cluster model [(TbtS)(OEt2)Fe4S3(2)(mu-STbt)(2)(mu(6)-S)] (2) [Tbt=2,4,6-trisbis(trimethylsilyl)methylphenyl] that is the closest synthetic mimic constructed to date. Of note is that two thiolate ligands and one hexacoordinated sulfide are connecting the two Fe4S3 incomplete cubanes similar to the native P-N-cluster, which has never been achieved. Cluster 2 has been characterized by X-ray crystallography and relevant physico-chemical methods. The variable temperature magnetic moments of 2 indicate a singlet ground state (S=0). The Mossbauer spectrum of 2 exhibits two doublets with an intensity ratio of 3:1, which suggests the presence of two types of iron sites. The synthetic pathway of the cluster 2 could indicate the native P-N-cluster maturation process as it has been achieved from the Fe4S4 cubane Fe4S4(STbt)(4) (1).
CRIS-Team WoS Importer:2021-06-18